Historical Roots Of The Formation Of The Art Of Music (Eurasian Journal of Humanities and Social Sciences, 2024)
In the context of the reforms being implemented in the new Uzbekistan, in order to popularize national musical art and musical instruments, restore musical melodies and musical instruments created by our ancestors, and especially to form a spiritual environment among young people, new music schools and higher educational institutions are being established, and international music festivals dedicated to national musical art and musical instruments are being organized in various directions in the cities of Samarkand, Shahrisabz, Boysun, and Khiva. Therefore, it is important to study the many years of experience accumulated by our people in creating national musical art and musical instruments in our country.